An alternative word-list for the Free and cued selective reminding test (FCSRT): list presentation and reliability study - Stoykova, Ralitsa; Matharan, Fanny; Raoux, Nadine; Amieva, Hélène (Gériatrie et psychologie neuropsychiatrie du vieillissement, 2013)
The Free and cued selective reminding test (FCSRT) is one of the most effective neuropsychological test used to assess verbal memory in elderly people with memory problems. There are currently two lists of words: the initial French version (list A) and an alternative one (list B). However, diagnosing early Alzheimer's disease in memory clinics often requires more than two evaluations, particularly in patients with very mild cognitive symptoms and patients with young onset disease. Usually, memory tests can be affected by practice effect, so several expositions of the same list of words could limit its clinical utility. The aim of our study was to create and validate a second alternative version (list C). The study sample was composed of 222 healthy volunteers aged from 17 to 84 years with a mean age of 44.6 years of whom 57% were females and 71% had a higher education. Within a two-month interval, each subject performed the test with one word-list and then the second one. The order of lists presentation was counterbalanced. Our findings indicate that the new alternative list (list C) is equivalent to the initial list of word (list A) for all the recall and recognition subscores, except the number of intrusive errors. This new list of words should be helpful to minimise potential practice effect and better assess memory decline in situations where the FCSRT has to be repeated across follow-up.